The Radiation Balance of Snow-Free Surfaces at Poste-de-la-Baleine, Québec, May 30 – June 1, 1970 - Wilson, Cynthia; MacFarlane, M. (Cahiers de géographie du Québec, 1971)
Total insolation and net radiation were measured for a wide variety of surfaces at Poste-de-la-Baleine, Québec, from May 30 to June 1, 1970, during alternating cyclonic and anticyclonic situations. With the exception of open water in southeastem James Bay and in the vicinity of the Belcher Islands, the ice cover was complete over Hudson Bayand westerly and southwesterly flow were associated with cool, wet, cloudy weather. For cloudy conditions, including fog and cirrus, and damp surfaces, a close linear relationship was found to exist between net radiation and total insolation for all surfaces. The results indicated that although the insolation was much reduced by cloud cover, about 72% of the energy was available at the surface for physical and biological processes. The importance of the sensible heat flux is noted, and of the cold advection from the Bay.